Thermal Optimization of Multilayer Furnace Walls under Transient Conditions - BOULKROUNE, Sofiane; CHAOUR, Mohamed; MAOUCHE, Hichem; CHERRAD, Mohamed Lotfi; ACHOUR, Toufik; BOUCHERMA, Djamel; HAMADI, Billel; CHORFI, Sofiane (International Journal of Computational and Experimental Science and Engineering, 2026)
This study presents an advanced numerical and optimization analysis of heat transfer in multilayer composite walls applied to high-temperature industrial furnaces. Unlike conventional approaches limited to parametric investigations, the present work integrates transient heat conduction with thermal performance optimization to identify optimal design configurations. The numerical simulations are performed using the finite element method (FEM) under realistic operating conditions representative of cupola furnaces. Special attention is given to the coupled effects of thermophysical properties and geometric parameters, particularly the thermal conductivity and thickness of the inner refractory layer. A multi-parameter optimization strategy is implemented to minimize heat losses and external wall temperature while maintaining structural constraints. The results demonstrate that the optimal configuration significantly enhances thermal insulation by increasing thermal resistance and reducing heat flux across the wall. Transient analysis further reveals the dynamic thermal response and energy storage capacity of the multilayer system, providing deeper insight into heat propagation mechanisms. The findings highlight the critical role of combined material selection and geometric optimization in improving energy efficiency. This study offers practical guidelines for the design of high-performance thermal insulation systems and contributes to the advancement of energy-efficient industrial furnace technologies. The optimized configuration achieved a reduction of up to 59% in external wall temperature and 61.84% in heat flux.